Merlin functions as a critical regulator in Staphylococcus aureus‐induced osteomyelitis. Issue 1 (11th August 2021) - Zhou, Zubin; Chen, Yuanliang; Min, Hong Sung; Wan, Yongbai; Shan, Haojie; Lin, Yiwei; Xia, Wenyang; Yin, Fuli; Jiang, Chaolai; Yu, Xiaowei
Abstract: Merlin is known as a tumor suppressor, while its role in osteomyelitis remains unclear. This study aimed to investigate the role of Merlin in Staphylococcus aureus ‐induced osteomyelitis and its underlying mechanisms. S. aureus ‐induced osteomyelitis mouse model was established in Merlin fl/fl Lyz2 cre/+ and Merlin fl/fl Lyz2 +/+ mice. Bone marrow–derived macrophages (BMDMs) were isolated and stimulated by lipopolysaccharide (LPS). Bioassays, including quantitative reverse transcription polymerase chain reaction (qRT‐PCR), Western blot analysis, and enzyme‐linked immunosorbent assays, were conducted to determine the levels of target genes or proteins. Immunoprecipitation was applied to determine the interactions between proteins. DCAF1 fl/fl mice were further crossed with Lyz2‐Cre mice to establish myeloid cell conditional knockout mice (DCAF1 fl/fl Lyz2 cre/+ ). It was found that the level of Merlin was elevated in patients with osteomyelitis and S. aureus ‐infected BMDMs. Merlin deficiency in macrophages suppressed the production of inflammatory cytokines and ameliorated the symptoms of osteomyelitis induced by S. aureus . Merlin deficiency in macrophages also suppressed the production of proinflammatory cytokines in BMDMs induced by LPS. The inhibitory effects of Merlin deficiency on the inflammatory response were associated with DDB1‐Cul4‐associated factor 1 (DCAF1). In summary, Merlin deficiency ameliorates S. aureus ‐induced osteomyelitis through the regulation of DCAF1. Abstract : Merlin deficiency suppressed the inflammatory response and symptoms of Staphylococcus aureus ‐induced osteomyelitis. The underlying mechanisms revealed that Merlin deficiency ameliorated S. aureus ‐induced osteomyelitis by regulating DDB1‐Cul4‐associated factor 1 (DCAF1).